2019
DOI: 10.1364/osac.2.002856
|View full text |Cite
|
Sign up to set email alerts
|

Observing the effect of polarization mode dispersion on nonlinear interference generation in wide-band optical links

Abstract: With the extension of the spectral exploitation of optical fibers beyond the Cband, accurate modeling and simulation of nonlinear interference (NLI) generation is of the utmost performance. Models and numerical simulation tools rely on the widely used Manakov equation (ME): however, this approach when considering also the effect of polarization mode dispersion (PMD) is formally valid only over a narrow optical bandwidth. In order to analyze the range of validity of the ME and its applicability to future wide-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Nevertheless, in this study we focus on a solution in a disaggregated network framework, where the signal transmitted through a specific OLS can be considered as fully Gaussian and depolarized, for each span. Under these conditions, it has been shown that the effect of PMD on the NLI generation is negligible [43], and that the small differences between the solutions of the Manakov equation and the DP-CNLSE do not vary significantly when enlarging the investigated bandwidth up to 4 THz. In this analysis we assume that the solutions of the Manakov equation and the DP-CNLSE are not significantly different when the C+L+S 1 -band transmission scenario is considered, as their differences do not depend on the overall bandwidth.…”
Section: Scalable and Disaggregated Approximate Modelmentioning
confidence: 97%
“…Nevertheless, in this study we focus on a solution in a disaggregated network framework, where the signal transmitted through a specific OLS can be considered as fully Gaussian and depolarized, for each span. Under these conditions, it has been shown that the effect of PMD on the NLI generation is negligible [43], and that the small differences between the solutions of the Manakov equation and the DP-CNLSE do not vary significantly when enlarging the investigated bandwidth up to 4 THz. In this analysis we assume that the solutions of the Manakov equation and the DP-CNLSE are not significantly different when the C+L+S 1 -band transmission scenario is considered, as their differences do not depend on the overall bandwidth.…”
Section: Scalable and Disaggregated Approximate Modelmentioning
confidence: 97%